PENGARUH MEDIA SOSIAL DAN DAYA TARIK WISATA TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN DOMESTIK DI PANTAI MELASTI, BALI - Ni Komang Krisnayani; Hanugerah Kristiono Liestiandre; I Gusti Putu Ade Pranjaya (JURNAL KEPARIWISATAAN, 2021)
The emergence of various kinds of social media has an impact on the industrial revolution in  the tourism sector, marked by the ease of accessing information through social media. The  tourism transformation of the 4.0 era changes the entire cycle of the tourism ecosystem,  especially in terms of the dissemination and consumption of information on social media  related to travel activities. The purpose of this research is to see the impact of media social and  tourist attraction on the domestic tourist visit-decision in Melasti Beach, Badung. This  research was designed using quantitative methods with multiple linear regression analysis.  Using qualitative and quantitative data, with total sample of 250 respondents from domestic  tourists visiting Melasti Beach. Sampling was done by distributing 30 questionnaires to visitors  at Melasti Beach. The analysis technique was tested using the classical assumption test. Most  of the respondents came from Jakarta, most of whom were women. The results of this study  indicate that there is an influence between social media and tourist attraction on the decision  to visit domestic tourists classified as positive.